2013
DOI: 10.1111/bjop.12044
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the bidirectional influences of leisure activity and memory in old people: A dissociative effect on episodic memory

Abstract: The present study examined the relationships between different types of social and cognitive activities and different types of episodic and semantic memory. A total of 794 adult men and women from five age cohorts (aged 65-85 at baseline), participating in the longitudinal Betula project on aging, memory, and health, were included in the study. The participants were studied over 10 years (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) in threes waves. Recognition and recall were used as epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 69 publications
1
17
0
1
Order By: Relevance
“…In all cases, the relationship between subjective memory ratings and objective cognitive performance represented a mutual influence of the two constructs on each other, with regard to sequential change over time. This study adds to a growing literature indicating that bidirectional influences are important in cognitive aging, including such paired constructs as cognition - activity level (Mousavi-Nasab, Kormi-Nouri, & Nilsson, 2014; Small et al, 2012; Wilson, Segawa, Boyle, & Bennett, 2012), cognition - physical functioning (Krall, Carlson, Fried, & Xue, 2014) and cognition - sense of well-being (Allerhand, Gale, & Deary, 2014). …”
Section: Discussionmentioning
confidence: 89%
“…In all cases, the relationship between subjective memory ratings and objective cognitive performance represented a mutual influence of the two constructs on each other, with regard to sequential change over time. This study adds to a growing literature indicating that bidirectional influences are important in cognitive aging, including such paired constructs as cognition - activity level (Mousavi-Nasab, Kormi-Nouri, & Nilsson, 2014; Small et al, 2012; Wilson, Segawa, Boyle, & Bennett, 2012), cognition - physical functioning (Krall, Carlson, Fried, & Xue, 2014) and cognition - sense of well-being (Allerhand, Gale, & Deary, 2014). …”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, social disconnection may be associated with poor cognitive functioning in later life [11]. Reduced frequency/quality of social contacts or closed interactions can lead to impairments in global cognitive function [12,13], executive function [14], episodic memory [15,16], and working memory (WM) [17]. Although a good social lifestyle has been found to protect against decline in some cognitive domains, its function is not totally clear [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies involving the same study sample have indicated that overall physical activity ( Josefsson et al, 2012 ) as well as general level of leisure activity, especially social activity, may protect against episodic memory decline in old age ( Mousavi-Nasab et al, 2014 ). However, certain leisure activities may be considered particularly interesting to consider as a potential moderator of age-related cognitive changes.…”
Section: Introductionmentioning
confidence: 99%